Case Report: Facial fracture sequelae: the importance of using a specific customized implant (PSI) for orbital reconstruction - Pulino, Bianca; Fonseca, Leonardo Alckmin Hotz; Vieira, Eduardo Hochuli; Piteri Filho, José Roberto; de Mâcedo, Thiago Felippe Oliveira; D'Amado, Marcelo Pigatto; Pereira, Rodrigo; Santos, Igor Alexandre Damasceno; Ilesan, Robert; Moreira, Henrique Cabrini; Viana, Drielli; Guerra, Raphael Capelli (Frontiers in Surgery, 2024)
The reconstruction of orbital fracture sequelae is a major challenge due to concerns regarding surgical approach and implant stability. Few anatomical sites of such minute size have presented with as much variation in treatment as the orbital floor fractures and related sequelae. Our patient developed sequelae of an orbital fracture over the last 3 years, presenting with dystopia, ophthalmoplegia, and diplopia in the supra- and lateroversion and aesthetic impairment. The variety of implant materials for reconstruction after orbital fractures is extensive, and the decision as to which material to use continues to be debated. The continuing development of computer-aided diagnosis and management and the construction of stereolithographic models offer comparable reproduction of anatomical detail. This technology is described in relation to the planning of trauma surgery and sequelae and the planning of ablative surgery for malignant neoplasms of the head and neck. The use of specific 3D printed titanium implants for bone defects was first reported in cranial reconstruction in 2012, and several studies have reported their use in orbital fractures. The advantages of this implant were increased stiffness, preventing shape loss during placement, a precise fit, and decreased surgical time. However, in the existing literature, the one-piece implant done in this way was a precise fit; therefore, it is possible that navigation between intraoperative anatomical landmarks is lost. However, in cases where reconstruction is difficult, such as extensive orbital wall fractures and large orbital sequelae, the 3D printed implant has been helpful in decreasing surgical time and can be accessed by a limited surgical approach with a precise fit. Our clinical case involved a 37-year-old male patient who experienced severe physical aggression in 2020, amid the COVID-19 pandemic. At the time, due to the overwhelming healthcare demands and resource constraints imposed by the pandemic, immediate surgical intervention for the correction of the fracture was not feasible. As a result of this delay, the patient developed sequelae of the orbital fracture over the last 3 years.